2018
DOI: 10.1332/204674317x14888886530269
|View full text |Cite
|
Sign up to set email alerts
|

Co-parenting arrangements in lesbian and gay families: when the ‘mum and dad’ ideal generates innovative family forms

Abstract: This paper engages with current debates on the potential of contemporary family formations, particularly those created by lesbian women and gay men, to challenge hegemonic family models. Drawing on in-depth interviews with lesbian and gay individuals living in Belgium, it explores parental ideals and family practices amongst people actively choosing "coparenting arrangements" which include more than two adults raising a child. It examines how this route to parenthood was justified by co-parents" desire for a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…A growing body of research focuses on parenting intentions, beliefs, and behaviors of lesbian, gay, and bisexual individuals in different countries (e.g. Herbrand, 2018 in Belgium; Wang & Zheng, 2021 in China) and different family forms (e.g. adoptive families, Pinderhughes & Brodzinsky, 2019).…”
Section: Limitations Future Directions and Conclusionmentioning
confidence: 99%
“…A growing body of research focuses on parenting intentions, beliefs, and behaviors of lesbian, gay, and bisexual individuals in different countries (e.g. Herbrand, 2018 in Belgium; Wang & Zheng, 2021 in China) and different family forms (e.g. adoptive families, Pinderhughes & Brodzinsky, 2019).…”
Section: Limitations Future Directions and Conclusionmentioning
confidence: 99%
“…The findings of the studies suggest that there are benefits to collaborative coparenting models of family for parents and children (see also Herbrand, 2017). In New Zealand and the UK, the kinds of complex situations emerging from such models could be resolved if legal provisions were made for more than two parents to be identified in law subject to the wishes of the parties concerned.…”
Section: Concluding Discussionmentioning
confidence: 96%
“…Elective co-parenting has received little academic attention, perhaps due to the ‘invisibility’ of these families, in that they resemble families that are co-parenting post-divorce/separation (Segal-Engelchin et al, 2005 ). Existing research on co-parenting has focussed on parental motivations for choosing elective co-parenting, finding that a key motivation for choosing co-parenting over other routes to parenthood (such as solo parenthood) is so that the child will have both a mother and father who are biologically related to the child (Erera & Segal-Engelchin, 2014 ; Herbrand, 2018a , 2018b ; Jadva et al, 2015 ; Ravelingien et al, 2016 ). Much of this research focuses on the experiences of LGBTQ + parents.…”
Section: Introductionmentioning
confidence: 99%
“…Much of this research focuses on the experiences of LGBTQ + parents. Whilst some research with queer and trans parents has found that co-parenting/polyamorous-parenting arrangements can enable resistance of traditional parenthood expectations (Bower-Brown, 2022 ; Pain, 2019 ; Vaccaro, 2010 ), other research with cis LGB parents highlights that many co-parents wish to create ‘traditional families’ (Herbrand, 2018a ). For instance, parents have been found to form families which privilege biogenetic parenthood and follow traditional gender norms (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation